(untitled) (Journal of Technology and Operations Management, 2025)
Germany is one of the countries in the Europe that has high coffee consumption. Bremen is one of the cities in Germany that is experiencing rapid growth in the coffee industry. Understanding consumer preferences when choosing a coffee shop is essential to support business growth and improve consumer experience. This research was initiated to answer the question of what factors most influence consumers’ decision to choose a café in Bremen. Factors such as coffee taste, ambience, price, and interior design are important. The study was conducted from October 2023 to January 2024, using non-probability sampling techniques or non-random sampling with a purposive sampling method. Conjoint analysis was employed in this study. The consumer preferences of coffee shop visitors in the City of Bremen are closely related to the important values that consumers choose when deciding on a purchase based on the order of important values. It is known that coffee shop consumers in the City of Bremen attach great importance on facilities, coffee shop atmosphere, location, price, coffee shop service and products.